KEKERABATAN Maxomys surifer (Miller 1900) ASAL SUMATRA, JAWA DAN KALIMANTAN BERDASARKAN VARIASI MORFOLOGINYA - Ibnu Maryanto; MH Sinaga (BERITA BIOLOGI, 1998)
Examination of morphological variation on Maxomys surifer from Sumatra, Jawa and Kalimantan were conducted using 60 adult specimens.Univariate and multivariate statistical analyses of 20 skull and four external characters showed that Maxomys surifer was not sexually dimorphic (P >0.05). The discriminant analysis based on skull characters indicated that Sumatran population had two distinct group; north (Ketambe and Tapanuli) and South to Central Sumatra, the north of Sumatra form was closer to Kalimantan and Jawa.